EFFECT OF HUMAN RESOURCES AND BUDGET IN PROJECT RISK MANAGEMENT FOR ENTERPRISE RESOURCE PLANNING SYSTEMS - Willy Cahya Sundara; R. Ati Haryati; Stanty Aufia Rachmat; Arman Syah Putra; Nurul Aisyah (Journal of Innovation Research and Knowledge, 2021)
Planning in a company is one of the most important things, because a good company must be well designed and planned, from the field of human resources to other parts such as sales, with careful planning will make the company not waste in terms of budget and company expenses, therefore the Enterprise Resource Planning System must be made to the maximum so that the company can be managed properly. The method used in this study uses a quantitative method using a questionnaire, which was conducted on 100 people who were selected at random in order to get real data from the field. The problem raised in this research is to test the human resources and budget variables on the Enterprise Resource Planning System, whether these variables affect significantly. This study produces data that can answer the research problem raised, namely the influence of human resource variables and budget variables on the Enterprise Resource Planning System, by knowing the variables that influence the company can improve the shortcomings of the current system.